2020
DOI: 10.1111/jvs.12849
|View full text |Cite
|
Sign up to set email alerts
|

Seed production and dispersal limit treeline advance in the Pyrenees

Abstract: Aims Pinus uncinata is the major treeline‐forming species in the Pyrenees. Yet, the role of its reproduction and dispersal as drivers of treeline dynamics remains unknown. Here we quantify seed production, dispersal and germination changes along the elevation gradient to assess whether they may constrain the foreseen treeline advance in the Pyrenees. Location Central Pyrenees, Catalonia, NE Spain. Methods We established four plots along an elevation gradient from the closed subalpine forest to the krummholz zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The first potential bottleneck to successful forest regeneration is viable seed production, which is largely governed by mature tree productivity and RA (Wenk & Falster, 2015). RA and seed production are sensitive to climate (Sirois, 2000;Roland et al, 2014) and are believed to contribute to limitation of tree distributions beyond alpine and polar tree line ecotones in some regions (Brown et al, 2019;Lantz et al, 2019;Anadon-Rosell et al, 2020;Körner, 2021). RA schedules, the changing magnitude of RA over a plant's lifetime, can vary dramatically among PFTs (Wenk & Falster, 2015;Rüger et al, 2020) and are adapted to specific disturbance regimes (Wenk & Falster, 2015), such that changing disturbance regimes can render an RA schedule nonviable (Lamont et al, 2020).…”
Section: New Phytologistmentioning
confidence: 99%
“…The first potential bottleneck to successful forest regeneration is viable seed production, which is largely governed by mature tree productivity and RA (Wenk & Falster, 2015). RA and seed production are sensitive to climate (Sirois, 2000;Roland et al, 2014) and are believed to contribute to limitation of tree distributions beyond alpine and polar tree line ecotones in some regions (Brown et al, 2019;Lantz et al, 2019;Anadon-Rosell et al, 2020;Körner, 2021). RA schedules, the changing magnitude of RA over a plant's lifetime, can vary dramatically among PFTs (Wenk & Falster, 2015;Rüger et al, 2020) and are adapted to specific disturbance regimes (Wenk & Falster, 2015), such that changing disturbance regimes can render an RA schedule nonviable (Lamont et al, 2020).…”
Section: New Phytologistmentioning
confidence: 99%
“…Although seed dispersal is the originating mechanism and has been recognized as a dominant spatial process controlling vegetation range shifts [33][34][35][36][37] , the impact of spatial proximity identified here might also be partially attributed to other spatially connected factors, such as active layer depth, soil thermal-hydro conditions, surface litter, nutrient availability, and herbivore activities [51][52][53][54] . These factors may contribute to the spatial connectivity of shrub expansion via rates of seed germination and seedling establishment.…”
Section: Discussionmentioning
confidence: 89%
“…Seeds can be dispersed through many biotic and abiotic vectors, such as gravity, animals, wind, ocean currents, and drifting sea ice, which result in dispersal ranges from meters to hundreds of kilometers 31,32 . Seed dispersal has been found important in explaining shifts in vegetation composition at sites in alpine 33 , mediterranean 34,35 , and tropical biomes 36,37 . Nonetheless, the impact of seed dispersal on vegetation patterns is also compounded by suitable environmental niches and thus is not always the limiting factor [38][39][40] .…”
Section: Mainmentioning
confidence: 99%
“…But, even here, environmental tolerances (to bioclimatic conditions) have predominated in assessing treeline dynamics (Holtmeier and Broll, 2020). Anadon‐Rosell et al (2020, this issue) study a treeline‐forming species in the Pyrenees and show the importance of seed production and seed dispersal in limiting the advance of the treeline. Interestingly, there was no clear effect of elevation on establishment dynamics, suggesting that dispersal processes are the main constraint on this treeline advancing under climate change.…”
Section: Dispersal In Spacementioning
confidence: 99%
“…It is common to consider dispersal separately from other processes governing the establishment, but these processes are intrinsically linked, as Korablev et al (2020, this issue) and Anadon‐Rosell et al, 2020, this issue) showed. Jara‐Guerrero et al (2020, this issue) demonstrated a functional link between dispersal syndrome, establishment and seed banking in Ecuadorian dry forest.…”
Section: Dispersal In Spacementioning
confidence: 99%